Becker's Dystrophy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
Two brothers affected with Becker's muscular dystrophy in whom the disease followed completely different courses are reported from the Departments of Neurology/Neurosurgery and Genetics, Washington University Medical School, St. Louis, MO.